Diagnosis of mycobacterium avium complex infection utilizing metagenomics next-generation sequencing: a case report - Li, Hongli; Wei, Luqing; Li, Fenge (Frontiers in Medicine, 2023)
Mycobacterium avium-intracellulare complex (MAC) is a type of nontuberculous mycobacteria (NTM), and is associated with underlying pulmonary diseases, such as chronic obstructive pulmonary disease, bronchiectasis, chronic aspiration or recurrent pneumonia, inactive or active tuberculosis, pneumoconiosis, as well as bronchogenic carcinoma. The risk factors for NTM-PD includes host, drug, and environmental factors. In this report, we present a case study of 61-year-old male patient who developed bilateral lung nodules and suffered from severe hemoptysis. Repeat acidfast bacilli test performed on both sputum and bronchoalveolar lavage fluid (BALF) samples showed negative result, as did GeneXpert test. We employed metagenomic next-generation sequencing (mNGS) to analyze lung nodule and BALF samples collected from the patient. Both samples tested positive for MAC within three days. In addition, traditional MAC culture was conducted for two months, which confirmed the growth of MAC in the patient's BALF. Then the patient was treated accordingly. Two months following treatment, high-resolution chest computed tomography revealed significant reduction in lung nodules of the patient. These results indicate that MAC-associated lung nodules were responsible for the patient's symptoms, and that clinicians should remain vigilant for MAC infection in male patient without predisposing conditions. Furthermore, these results highlight the potential utility of mNGS as a promising fast diagnostic tool for MAC infection, as well as its potential role in the diagnosis of NTM disease.